2015
DOI: 10.1371/journal.pone.0131486
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography (PET) Quantification of GABAA Receptors in the Brain of Fragile X Patients

Abstract: Over the last several years, evidence has accumulated that the GABAA receptor is compromised in animal models for fragile X syndrome (FXS), a common hereditary form of intellectual disability. In mouse and fly models, agonists of the GABAA receptor were able to rescue specific consequences of the fragile X mutation. Here, we imaged and quantified GABAA receptors in vivo in brain of fragile X patients using Positron Emission Topography (PET) and [11C]flumazenil, a known high-affinity and specific ligand for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…Loss of the thalamic gamma oscillator, and weaker or less refined thalamocortical input are likely contributors to the loss of EGOs. Thalamus is the region with the largest reduction of GABA A receptor binding in FXS patients 43 . Fragile X granules are expressed in thalamocortical axons in mouse (but not in thalamic interneurons or reticular neurons) 44 and glutamatergic synaptic development at thalamocortical synapses is delayed in FMR-KO mice 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Loss of the thalamic gamma oscillator, and weaker or less refined thalamocortical input are likely contributors to the loss of EGOs. Thalamus is the region with the largest reduction of GABA A receptor binding in FXS patients 43 . Fragile X granules are expressed in thalamocortical axons in mouse (but not in thalamic interneurons or reticular neurons) 44 and glutamatergic synaptic development at thalamocortical synapses is delayed in FMR-KO mice 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In the Drosophila model, limited research available has demonstrated that a GABA A receptor reduction can lead to behavioral impairments. However, other research from FXS models indicated that the mechanism was likely more complicated and possibly indirect due to not only variable GABA metabolisms but also regional specificity [ 40 , 42 , 43 ]. For example, vision process is modulated by different GABA receptors in spread brain via tonic inhibition, such as temporal cortex, lateral geniculate nucleus (LGN) of the thalamus, and vision cortex [ 44 , 45 ], while tonic inhibition is mediated via extrasynaptic α 5- and δ -containing GABA A Rs [ 40 , 44 ].…”
Section: Decreased Expression Of Gaba Receptor Subunits In Fxs Modmentioning
confidence: 99%
“…First, we have taken a fixed value of glutamate−GABA concentration over the entire brain commensurate with measurements from MRS using single-voxel spectroscopy. However, the concentrations of these neurotransmitters are variable across different areas which can be measured from positron emission tomography (PET) recordings (D'Hulst et al, 2015). Nonetheless, a detailed analysis with glutamate−GABA values in individual brain areas contributing to resting-state dynamics remains out of the scope at this point due to lack of availability of detailed data but will be an interesting issue to resolve in future as wand when such data is available.…”
Section: Discussionmentioning
confidence: 99%